The bacteria inside human cancer cells: Mainly as cancer promoters - Zhu, Wei; Wang, Jing-Zi; Liu, Zhixian; Wei, Ji-Fu (Frontiers in Oncology, 2022)
The roles of the microbiome in human being have becoming clearer with the development of next-generation sequencing techniques. Several evidences showed strong correlations between microbiome and human health and disease, such as metabolic disorders, infectious diseases, digestive system diseases and cancers. Among these diverse microbiomes, the role of bacteria in human cancers, especially in cancer cells has received extensive attention. Latest studies found that bacteria widely existed in cancers, mainly in cancer cells and immune cells. In this review, we summarize the latest advances in understanding the role of bacteria in human cancer cells. We also discuss how bacteria are transported into cancer cells and their physiological significance in cancer progression. Finally, we present the prospect of bacterial therapy in cancer treatment.